Energy balance in irrigated and non-irrigated soybeans - Fontana, Denise Cybis; Berlato, Moacir A.; Bergamaschi, Homero (Pesquisa Agropecuaria Brasileira, 1991)
Components of the energy balance were determined in a micrometeorological experiment established with Bragg soybeans cultivar, grown under irrigated (2,500 m2 plot) and non-irrigated (2,100m2) conditions at Taquari, RS, Brazil, in 1985/86. The non-irrigated treatment was subjected to a drought period from sowing up to full flowering period. The use of the net radiation differed among treatments, being affected by the soil water potential and the atmospheric evaporative demand. A great portion of the net radiation was occounted for the evaporation latent heat flux, being 95% and 78% for the irrigated and non-irrigated plots, respectively. The soil heat flux accounted for the least portion of the energy balance, being 2% and 7% for the irrigated and non-irrigated plots, respectively.